Respuestas
Respuesta dada por:
28
Espero que sirva
Te lo dejo en el archivo :)
Te lo dejo en el archivo :)
Adjuntos:
![](https://es-static.z-dn.net/files/d9e/ecb9444b0403ce06e7d7202f82f84698.jpg)
Respuesta dada por:
18
(x + 1)(2x+ 5) = (2x + 3)(x - 4) +5 =>
2x^2 + 5x +2x +5 = 2x^2 -8x + 3x -12 + 5 =>
2x^2- 2x^2 + 7x + 8x -3x +5 +12 -5 = 0 =>
12x +12 = 0 =>
12x= -12 =>
x = -12/12 =>
x = -1
2x^2 + 5x +2x +5 = 2x^2 -8x + 3x -12 + 5 =>
2x^2- 2x^2 + 7x + 8x -3x +5 +12 -5 = 0 =>
12x +12 = 0 =>
12x= -12 =>
x = -12/12 =>
x = -1
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años